Optimation of Tank Model's Parameters - Budi I. Setiawan (PERTETA, 2003)
Tank to model is one of hydrological models to analize characteristics of river flow. The model can give information of water availability and be used to predict flood occurences. As it is setting the embodied parameters. In from of Standard Tank Model, the number of parameters accounts to 12. Many optimation method available for general application. This paper introduces an optimation technique to determine the parameters with taking into account confornity to water balance in addition to best-fifting. Here, two data from Cidanau and Terauchi Watershed were used for clarification, which show that this optimation technique gained fast and accurate result. This technique has been made available to use in form of an application sofware and openly possible to accomodate the other forms of Tank Model.